Invasive Tree Pests Devastate Ecosystems—A Proposed New Response Framework - Bonello, Pierluigi; Campbell, Faith T.; Cipollini, Don; Conrad, Anna O.; Farinas, Coralie; Gandhi, Kamal J. K.; Hain, Fred P.; Parry, Dylan; Showalter, David N.; Villari, Caterina; Wallin, Kimberly F. (Frontiers in Forests and Global Change, 2020)
Maintenance and restoration of forest ecosystems will be key to achieving necessary carbon sequestration goals, protecting biodiversity, and supporting healthy economies and societies. Forest ecosystems are increasingly threatened by non-native forest insects and pathogens. A portion of these pests are able to overcome prevention and containment efforts and become established in naïve ecosystems. Once established these pests pose a long-term large-scale threat to forest ecosystems, which current policy and response frameworks are poorly equipped to address. We propose the creation of a federal Center for Forest Pest Control and Prevention to implement end-to-end responses to forest pest invasions using an ecologically-informed framework that fully integrates host tree resistance development and deployment.